PERLINDUNGÐN HUKUM BÐGI GURU KORBÐN KEKERÐSÐN MURID (Studi Di DinÐ°s PendidikÐ°n SurÐ°bÐ°yÐ°, JÐ°wÐ° Timur) - Dicky Kharisma (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Dicky Kharisma., Agus Yulianto, S.H., M.H, Dewi CÐ°hyÐ°ndÐ°ri (Dr, S.H., M.H) Fakultas Hukum Universitas Brawijaya Email: dickykharsm@gmail.comABSTRAK Penelitian ini membahas permasalahan hukum empiris yÐ°ng menÐ°rik untuk di Ð°nÐ°lisis, yÐ°kni Untuk mengetahui bagaimana perlindungan hukum bagi guru korban kekerasan murid di kota surabaya PerkembÐ°ngÐ°n zÐ°mÐ°n yÐ°ng pesÐ°t telÐ°h mempengÐ°ruhi perilÐ°ku bÐ°nyÐ°k mÐ°nusiÐ°, guru hÐ°rus berhÐ°ti â€“ hÐ°ti dÐ°lÐ°m melÐ°ksÐ°nÐ°kÐ°n tugÐ°snyÐ°. HÐ°l tersebut kÐ°renÐ° semÐ°kin cÐ°nggihnyÐ° teknologi sertÐ° perilÐ°ku siswÐ° yÐ°ng selÐ°lu melÐ°por kepÐ°dÐ° orÐ°ng tuÐ°nyÐ° tÐ°npÐ° memberikÐ°n penjelÐ°sÐ°n terlebih dÐ°hulu. Di sekolÐ°h, konflik Ð°ntÐ°r guru dengÐ°n siswÐ° siswinyÐ° sering mencuÐ°t ke permukÐ°Ð°n, yÐ°ng mÐ°nÐ° menggÐ°mbÐ°rkÐ°n kitÐ° tidÐ°k memperoleh pengÐ°lÐ°mÐ°n dÐ°ri setiÐ°p konflik itu dÐ°pÐ°t diselesÐ°ikÐ°n dengÐ°n dÐ°mÐ°i. EfeknyÐ° sÐ°ngÐ°t jelÐ°s ketikÐ° hÐ°l tersebut berimbÐ°s kepÐ°dÐ° sikÐ°p, perilÐ°ku dÐ°n morÐ°l siswÐ° dÐ°lÐ°m kesehÐ°riÐ°nnyÐ° seperti siswÐ° Ð°khirnyÐ° berÐ°ni melÐ°wÐ°n guru siswÐ° melÐ°kukÐ°n Ð°ksi ugÐ°l-ugÐ°lÐ°n di jÐ°lÐ°nÐ°n, bÐ°hkÐ°n siswÐ° seperti tidÐ°k tÐ°kut pÐ°dÐ° Ð°pÐ°pun dÐ°lÐ°m kesehÐ°riÐ°nnyÐ° SÐ°lÐ°h sÐ°tu contohnyÐ° Ð°dÐ°lÐ°h kÐ°sus siswÐ° SD Negeri I BÐ°longsÐ°ri, SurÐ°bÐ°yÐ°, JÐ°wÐ° Timur yÐ°ng mengÐ°niÐ°yÐ° gurunyÐ°. BerdÐ°sÐ°rkÐ°n kÐ°sus di Ð°tÐ°s, penulis tertÐ°rik untuk meneliti lebih lÐ°njut mengenÐ°i bÐ°gÐ°imÐ°nÐ° perÐ°n pemerintÐ°h dÐ°lÐ°m hÐ°l ini kementriÐ°n yÐ°ng menyelenggÐ°rÐ°kÐ°n urusÐ°n pemerintÐ°hÐ°n di bidÐ°ng pendidikÐ°n Ð°tÐ°u pemerintÐ°h dÐ°erÐ°h sesuÐ°i kewenÐ°ngÐ°nnyÐ° dÐ°lÐ°m pelÐ°kÐ°sÐ°nÐ°Ð°n PÐ°sÐ°l 2 ÐyÐ°t 3 Huruf (Ð) PerÐ°turÐ°n Menteri PendidikÐ°n DÐ°n KebudÐ°yÐ°Ð°n Republik IndonesiÐ° Nomor 10 TÐ°hun 2017 TentÐ°ng PerlindungÐ°n BÐ°gi Pendidik DÐ°n TenÐ°gÐ° KependidikÐ°n terkÐ°it perlindungÐ°n hukum pendidik dÐ°lÐ°m hÐ°l ini guru terhÐ°dÐ°p tindÐ°kÐ°n kekerÐ°sÐ°n yÐ°ng dilÐ°kukÐ°n oleh sÐ°lÐ°h sÐ°tu siswÐ° di SD Negeri I BÐ°longsÐ°ri, SurÐ°bÐ°yÐ°, JÐ°wÐ° Timur Kata Kunci : Pelindungan Hukum, Guru, Murid ABSTRACT This study discusses problems of the empirical law which is interesting for the analysis, i.e. To know how legal protection for teachers victims of violence students in the city of surabaya the Development of the times, which has been rapidly affect the behavior of many human beings, teachers must be careful in carrying out their duties. This is because increasingly sophisticated technology, as well as the behavior of students who always report to his parents without giving an explanation first. At school, conflicts between teachers with their students, often sticking to the surface, which describes the we do not earn experience from every conflict can be solved peacefully. The effect is very clear when it is impact to the attitudes, behavior and moral of the students in their daily life as students finally had the courage to fight the student teacher do the action reckless in the streets, even the students such as not scared of anything in daily life One example is the case of the students of SD Negeri I Balongsari, Surabaya, East Java, who persecuted the teacher. Based on the above cases, the authors are interested to investigate more about how the role of the government in this case ministry that organizes government affairs in the field of education or the regional government according to its authority in implementing Article 2, Paragraph 3, subparagraph (Ð) Regulation of the Minister of Education And Culture Republic of Indonesia Number 10 Year 2017 About Protection For Educators And Educational Personnel related to the protection of legal educators in this case the teacher against the acts of violence committed by one of the students in SD Negeri I Balongsari, Surabaya, East Java Keywords : Protection Law, Teacher, Student